Soil Structure and Carbon Pools in Response to Common Tropical Agroecosystems - Handayani, Iin Purwati; Prawito, Priyono (JOURNAL OF TROPICAL SOILS, 2013)
Maintaining soil physical properties and organic C is the goal for sustainable use of soil resources in agroecosystems. The objectives of this research were to evaluate the changes in soil structure and C pools and to quantify the availability of labile C pools. The study site was in Bengkulu Province Sumatra, Indonesia. Four common agroecosystems were used to determine soil physical properties including bulk density, porosity, and soil aggregates. Labile soil C pools examined were particulate organic C (POC), microbial biomass C (MBC) and C mineralization (C min). Farming practices significantly affected the bulk density, macro-porosity, micro-porosity, aggregate stability(AS), mean weight diameter (MWD) and aggregation ratio (AR). However, the responses from treatments depend upon the soil depth. In general, agroforestry and fallow fields provided lower bulk density, higher porosity, AS, MWD and AR compared to rubber tree plantation and grain cropping. As a general trend, the values of POC, MBC and C min decreased in the order of agroforestry > fallow field > rubber tree plantation > grain cropping. The order of labile C pools in all fields were POC > MBC > C min. Significant increases (32 – 62%, p<0.05) in the soil organic C content was observed in agroforestry and fallow fields compared to rubber tree plantation and grain cropping systems at the depth of 0 – 20 cm. The highest available POC (43 to 82%) and MBC (2 to 5%) were found in agroforestry and fallow field. Mineralized C was about 2% in all fields indicating similar amount of active C from soil organic matter. In conclusion, improvement in soil structure properties, TOC, POC and MBC in agroforestry andfallow fields indicates better soil C sequestration and soil quality in these agroecosystems.Keywords: Aggregation, carbon mineralization, microbial biomass carbon, particulate organic carbon,  rubber plantation[How to Cite: Handayani IP and P Prawito. 2013. Soil Structure and Carbon Pools in Response to Common Tropical Agroecosystems. J Trop Soils 18 (2): 105-113. Doi: 10.5400/jts.2013.18.2.105][Permalink/DOI: www.dx.doi.org/10.5400/jts.2013.18.2.99]REFERENCESAhn MY, AR Zimmerman, NB Comerford, JO  Sickman and S Grunwald.  2009.  Carbon mineralization and labile organic carbon labile pools in the sandy soils of north Florida watershed. Ecosystems 12: 672-685.  Anderson JPE. 1982.  Soil Respiration. In: AL Page, RH Miller and DR Keeney(eds).  Methods of Soil Analysis part 2, chemical and microbiological properties, 2nd ed. American Society of Agronomy and Soil Science Society of America.  Madison, WI, pp. 831-872.Anderson TH and KH Domsch.  1990.  Application of ecophysiological quotients (qCO2 and qD) on microbial biomass from soils of different cropping histories.  Soil Biol Biochem 22: 251-255.Baker BJ, NR Fausey and KR Islam.  2004.  Comparison of soil physical properties under two different water table management regimes.  Soil Sci Soc Am 68: 1973-1981.Balesdent  J, C Chenu and M Balabane.  2000.  Relationship of soil organic matter dynamics of physical protection on tillage.  Soil Till Res 53: 215-230.Batjes NH.  1996.  Total C and N in soils of the world.  Eur J Soil Sci 47: 151-163.Bauhus J, D Pare and I Cote.  1998.  Effect of tree species, stand age and soil type on soil microbial biomass and its activity in a southern boreal forest.  Soil Biol Biochem 30: 1077-1089.Bayer C, L Martin-Neto, CN Pillon and L Saugoi.  2001.  Changes in Soil Organic Matter Fractions under Subtropical No-Till Cropping Systems.  Soil Sci Soc Am J 65: 1473-1478.Bowen GD and AD Rovira.  1991.  The rhizosphere.  The hidden half of the hidden half.  In: Y Waisal, ,A  Eshel and U Kafkafi  (eds). Plant Roots: the Hidden Half.  Marcel Dekker, New York, pp. 641-669.Cambardella  CA and ET  Elliot.  1992.  Particulate soil organic-matter changes across a grassland cultivation sequence.  Soil Sci Soc Am J 56: 777-783.Castro H,  CA  Cambardella  and ET  Elliot.  2010.  Carbon and nitrogen distribution in aggregates from cultivated and native grassland soil.  Soil Sci Soc Am J  57: 1071-1076.Eynard A, TE Schumacher, RA Kohl and DD Malo.  2006. Soil wettability relationships with soil organic carbon and aggregate stability. Proceedings of the 18th World Congress of Soil Science, Philadelphia, July 9-15, Pennyslavia, USA.Franzluebbers  AJ.  2002.  Soil organic matter stratification ratio as indicator of soil quality.  Soil Till Res 66: 95-106. Gajda AM.  2008.  Effect of different tillage systems in some microbiological properties of soils under wheat.  Int Agrophysics 22:  201-208.Gregorich  EG, MR Carter, DA Angers, CM  Monreal and BH Ellert. 1994.  Towards a minimum data set to assess soil organic matter quality in agricultural soils.  Can J Soil Sci 74: 367-385. Handayani  IP.  2004.  Soil quality changes following forest clearance in Bengkulu Sumatra.  Biotropia 22: 15-28.Handayani IP, MS  Coyne, CD Barton and S Workman.  2008.  Soil Carbon Pools and Aggregation Following Stream Restoration in A Riparian Corridor: Bernheim Forest, Kentucky.  J Environ Monitor Restor 4: 11-28.Handayani IP, P Prawito and M Ihsan.  2012.  Soil changes associated with Imperata cylindrica grassland conversion in Indonesia.  Int J Soil Sci 7: 61-70.Handayani IP, MS Coyne, and T Phillips. 2011. Soil organic carbon fractions differ in two contrasting tall fescue systems. Plant and Soil 338: 43-50.  doi: 10.1007/s11104-0100352-z.Houghton  RA and CL  Goodale.  2004.  Effect of land use change on the carbon balance of terrestrial ecosystems.  Ecosystems and Land Use Change, Geographical Monograph Series 153: 85-98.Huang  X, EL Skidmore and GL Tibke.  2002.  Soil quality of two Kansas soils as influenced by the Conservation Reserve Program.  J Soil Water Conserv 57: 344-350.  Jenkinson  DS and JN Ladd.  1981.  Microbial biomass in soil:measurement and turnover.  In: EA Paul and JN Ladd (eds). Soil Biochemistry Vol. 5. Marcel Dekker, NY, pp. 415-471. Jinbo  Z, S Changchun and Y  Wenyan.  2007.  Effects of cultivation on soil microbial properties in a freshwater march soil in Northeast China.  Soil Till Res 93: 231-235.Klute A.  1986.  Methods of soil analysis- Part 1.  Physical and Mineralogical Methods. 2nd. American Society of Agronomy and Soil Science Society of America.  Agronomy Series 9.  Madison, WI, 1188 p.Kosmas  C, St Gerontidis and M Marathianou.  2000.  The effect of land use change on soils and vegetation over various lithological formations on Lesvos (Greece).  Catena 40: 51-68. Li XG, PL  Zhang, P Yin, YK  Li, QF  Ma, RJ  Long and FM  Li.  2009.  Soil organic  carbon and nitrogen fractions and water-stable aggregation as affected by cropping and grassland reclamation in an arid sub-alpine soil.  Land Degrad Dev 20: 176-186.Li Y and BW Mathew.  2010.  Effect of conversion of sugarcane plantation to forest and pasture on soil carbon in Hawaii.  Plant Soil 335: 245-253.Lopez-Bermudez  F, A  Romero-Diaz, J  Martinez-Fernandez and J  Martinez-Fernandez. 1996.  The El Ardal field site:soil and vegetation cover. In: CJ Brandt and JB Thornes (eds).  Mediterranean Desertification and Land Use.  John Wiley and Sons, Chichester, pp. 169-188.Luxmoore  RJ.  1981.  Micro-, meso-, and macroporosity of soil.  Soil Sci Soc Am J 45: 671-672.Mazzarino  MJ, L Szott and M Jimenez.  1993.  Dynamics of soil total C and N, microbial biomass and water soluble C in tropical agro ecosystems.  Soil Biol Biochem 25: 205-214.McLauhan  KK, SE Hobbie and WM Post.  2006.  Conversion from agriculture to grassland builds soil organic matter on decadal timescales.  Ecol Appl 16: 143-153.  Mohammadi  K.  2011.  Soil microbial activity and biomass as influenced by tillage and fertilization in wheat production.  Am-Euras J Agric Environ Sci 10: 330-337.Paul  EA and FE  Clark.  1996.  Soil Microbiology and Biochemistry.  Academic, San Diego, CA.Preger AC, R Kosters, CC  Du Preez, S  Brodowski and W  Amelung.  2010.  Carbon sequestration in secondary pasture soils: a chronosequence study in the south African Highveld.  Eur J Soil Sci 61: 551-562.Puget  P, C  Chenu and J Balesdent.  2000.  Dynamics of soil organic matter associated with particle-size fractions of water-stable aggregates.  Eur J Soil Sci 51: 595-605.SAS Institute.  2007.  SAS User’s Guide: Statistics.  SAS Inst., Cary, NC. Saviozzi  A, P  Bufalino, R Revi-Minzi and R  Riffaldi. 2002. Biochemical activities in a degraded soil restored by two amendments: a laboratory study. Biol Fertil Soils 35: 96-101.Sharrow  SH and S Ismail.  2004.  Carbon and nitrogen storage in western Oregon agroforests, forests, and pastures.  Agroforest Syst 60: 123-130. Shrestha  BM, BR  Singh, BK Sitaula, R  Lal and RM  Bajracharya.  2007.  Soil aggregate- and particle- associated organic carbon under different land uses in Nepal.  Soil Sci Soc Am J  71: 1194-1203.Six  J, RT Conant, EA  Paul and K Paustian.  2002.  Stabilization mechanisms of soil organic matter: implications for C-saturation of soils.  Plant Soil 241: 155-176.Skidmore  EL, WA  Carstenson and EE  Banbury.  1975.  Soil changes resulting from cropping.  Soil Sci Soc Am J 39: 964-967.Sparling  GP.  1992.  Ratio of microbial biomass carbon to soil organic carbon is sensitive indicator changes in soil organic matter.  Aust J Soil Res 30: 195-207.Staben  ML, DF  Bezdicek, MF Fauzi and  JL Smith. 1997.  Assessment of soil quality in conservation reserve program and wheat-fallow soils.  Soil Sci Soc Am J 61: 124-130.Su YZ, WJ  Liu, R Yang and XX  Chang.  2009.  Changes in soil aggregate, carbon, nitrogen following the conversion of cropland to alfalfa forage land in the marginal Oasis of Northwest China.  Environ Manage 43: 1061-1070.Templer  PH, PM Groffman and AS  Flecker.  2005.  Land use change and soil nutrient transformations in the Los Haitises region of the Dominican Republic.  Soil Biol Biochem 37: 215-225.Wander   MM and GM Bidart.  2000.  Tillage practice influences on the physical protection, bioavailability and composition of particulate organic matter.  Biol Fertil Soils 32: 360-367.Wang  B, GB Liu, S  Xue and B Zhu.  2011.  Changes in soil physic-chemical and microbiological properties during natural succession on abandoned farmland in the Loess Plateau.  Environ Earth Sci 62: 915-925.Yadav RS, BL Yadav and BR Chhipa.  2008.  Litter dynamics and soil properties under different tree species in a semi-arid region of Rajasthan, India.  Agroforest Syst 73: 1-12.Zhang K, H Dang, S Tan, Z Wang and Q Zhang.  2010.  Vegetation community and soil characteristics of abandoned agricultural land and pine plantation in the Qinling Mountains china.  For Ecol Manage 259: 2036-2047.Zhu B, Z  Li, P Li, G Xu and S  Xue.  2010.  Soil erodibility, microbial biomass, and physical-chemical property changes during long-term natural vegetation restoration: a case study in the Loess Plateau China.  Ecol Res 25: 531-541.